The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.actamat.2017.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of nanoporous gold in tension

Abstract: We report results of the tensile properties of nanoporous gold (NPG) as a function of the density and average ligament diameter. As-dealloyed tensile samples were thermally treated to coarsen the length scale of the NPG structure while increasing the sample density resulting from thickness reductions. The behaviors of samples with mean ligament diameters ranging from 30-750 nm and corresponding densities ranging from 0.30-0.57 that of bulk gold were examined. Digital image analysis was used to obtain ligament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 33 publications
3
53
1
Order By: Relevance
“…Ashby plot showing the Young's modulus and density of metals, metal foams, polymers, and metal–polymer hybrid composite nanopillars as reported by Dusoe et al The light gold composites as reported herein fill the white space between the metallic and polymeric materials as indicated in gray.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Ashby plot showing the Young's modulus and density of metals, metal foams, polymers, and metal–polymer hybrid composite nanopillars as reported by Dusoe et al The light gold composites as reported herein fill the white space between the metallic and polymeric materials as indicated in gray.…”
Section: Resultssupporting
confidence: 51%
“…Fabrication of Organic-Inorganic Aerogel: After diffusion of salt for 24 h, the gel was placed in an aluminum cage directly in the salt bath for 1 h to ensure all fibril entanglement points were converted into crosslinks. The cage with the hydrogel was then transferred into 50% EtOH and 50% pH 2 milli-Q water bath (100 mL) for 24 h. This was followed by [53] showing the Young's modulus and density of metals, [46] metal foams, [49,54,55] polymers, [47,48] and metal-polymer hybrid composite nanopillars as reported by Dusoe et al [52] The light gold composites as reported herein fill the white space between the metallic and polymeric materials as indicated in gray. two subsequent transfers into 99% EtOH (100 mL) for 24 h to complete the solvent exchange.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…To compare NPG models, different structural properties can be used, such as the ligaments diameter distribution (D m ), the scaled genus density (g v ) which quantifies the connectivity, and the interfacial shape distribution (ISD) which is the dis-tribution of the local curvature of the ligaments and characterizes the morphology. The structural properties of NPG are highly correlated to mechanical or catalytic properties [1,15,24]. Models can also be compared on the basis of mechanical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanoporous (NP) materials present interesting perspectives owing to their nanometric-size microstructure and large specific surface (extremely high open-porosity level). From the first feature, mechanical strength, unique plasticity, and multiphysical properties are expected [1][2][3][4][5]. The second is related to surface interactions and chemical reactivity, with perspectives in domains such as electrochemical energy storage and conversion, catalysts [6,7], biomedical implants [8], and filtering and purification [9].…”
Section: Introductionmentioning
confidence: 99%